Novel use of social media to assess and improve coastal flood forecasts and hazard alerts - J. M. Brown (Nature Portfolio, 2021)
Abstract Coastal communities and infrastructure need protection from flooding and wave overtopping events. Assessment of hazard prediction methods, used in sea defence design, defence performance inspections and forecasting services, requires observations at the land-sea interface but these are rarely collected. Here we show how a database of hindcast overtopping events, and the conditions that cause them, can be built using qualitative overtopping information obtained from social media. We develop a database for a case study site at Crosby in the Northwest of England, use it to test the standard methods applied in operational flood forecasting services and new defence design, and suggest improvements to these methods. This novel approach will become increasingly important to deliver long-term, cost-effective coastal management solutions as sea-levels rise and coastal populations grow. At sites with limited, or no, monitoring or forecasting services, this approach, especially if combined with citizen science initiatives, could underpin the development of simplified early warning systems.